Control on (U-234/U-238) in lake water: A study in the Dry Valleys of Antarctica - Henderson, G; Hall, B; Smith, A; Robinson, L (2006)
The (234U/238U) ratio in surface waters is generally higher than secular equilibrium due to nuclide recoil during alpha-decay of 238U. The size of the deviation from secular equilibrium contains information about the environment in which the water is found. This potential tool for environmental reconstruction has previously been studied in rivers, groundwater, and sediment pore-water. Here we conduct a first assessment of the controls on (234U/ 238U) in lakewaters. Thirty-three waters from glacial melt, streams, and lakes of the McMurdo Dry Valleys (Antarctica) were analysed for U concentration and isotope ratio. Glacial melt has a low U concentration and a (234U/238U) identical to seawater, suggesting that U in Antarctic ice is largely sourced from sea-salt aerosols. Stream waters have higher U concentration (0.009 to 1.282 ppb) and (234U/238U) (1.280 to 1.832) due to chemical weathering of sediment in stream channels and 234U recoil from this sediment. Average (234U/238U) is 1.502, close to the average of observations from other surface waters worldwide. The absence of groundwaters in the Dry Valleys indicates that reasonably high (234U/238U) ratios do not require groundwater sources of U, so care should be taken before using high (234U/238U) as an indicator of groundwater inputs to stream waters. Lakewaters have U concentrations ranging from 0.027 to 46 ppb (i.e. up to 14 times the seawater concentration) and (234U/238U) from 1.05 to 4.50. Young lakes have (234U/238U) which reflects the sources of U. In one case (Lake Joyce) a (234U/238U) lower than seawater may suggest U sourced from melting of old ice in which 234U excess has partially decayed. In older lakes, (234U/238U) is significantly higher than that in the inputs due to addition of recoil 234U from sediments underlying the lake. The size of the deviation from secular equilibrium can only be explained, however, if recoil from a large area of sediment is considered. This is reasonable for the two lakes with particularly high (234U/238U) (Bonney, Vanda) which are both relicts of much larger lakes present during the last glacial period. On the basis of this study, the addition of recoil 234U to lake water is expected to be a general feature, and to cause a noticeable increase in (234U/238U) for lakes with a U residence time of more than a few thousand years. © 2005 Elsevier B.V. All rights reserved.